Modeli postavitve knjižničnega gradiva v slovenskih splošnih knjižnicah s posebnim ozirom na postavitev gradiva v mladinskih oddelkih - Kobal, Marija (Knjižnica, 2009)
The classification and the alignment of library material represent an important part of the library science from its early beginnings onwards. The introduction of UDC into Slovene public libraries coincided with the alteration of the open access library collection. In Slovenia the public libraries in average take into account the references and recommendations for the arrangement of the free access library collection, considering the age groups of the users, adults and juniors. The next division is connected with the functional type of the material, which is divided into fiction, and scientific materiaal, and then there is the UDC label for the arrangement of the material on the shelves or word systematic in one of the public libraries. In the junior department there is a need for a further division into four age/reading groups of books instead of three. Within the formed groups there is the further arrangement of books in an alphabetical order by means of author or subject headings. The public library is a unit, which services all the residents in its local area. The different needs and interests of users should take into account in the formation of a library material arrangement.
Keywords: splošne knjižnice; prosti pristop; klasifikacija; postavitev gradiva; univerzalna decimalna klasifikacija